FFECTS OF VARIED INTENSITIES OF WALKING AND JOGGING PROGRAMME ON RESTING PULSE RATE AMONG THE MIDDLE AGED MEN. - K. Ramakrishnan and A. M. Antony (PESY, 2014)
The reason of the present investigation was to observe the “effects of varied intensities of walking and jogging programme on Resting Pulse Rate among the middle aged men.” Sixty middle-aged men from Palakad Town, Kerala, were selected as subjects at random. The age of the subjects ranged from 35to58years. The selected subjects were divided into three experimental groups and a control group. Group -I designed for Low Intensity of Walking and Jogging (LI-WJ) group – II designed for Moderate Intensity of Walking and Jogging group (MI- WJ), Group – III designed for High Intensity of Walking and Jogging group (HI-WJ) and Group – IV served as control group (CG). The Resting Pulse Rate was chosen as criterion variable. All the subjects of four groups were tested on Resting Pulse Rate at prior and immediately after the programme of twelve weeks. The data was collect for all the groups on Resting Pulse Rate by using radial pulse count; the unit of the measurement was in beats per minute. The data were collect from the four groups before and after the training programme. Analysis of covariance was use to find out the adjusted post test mean difference of four groups, and Scheffe’s post hoc test was used to find out pair-wise comparisons between groups. The study revealed that there was a significant difference among the low intensity, moderate intensity, high intensity of walking and jogging group and control croup. Moderate intensity of walking and jogging programme was more influenced on the performance of resting pulse rate among the middle-aged men population.